One-Pot Synthesis of Dimannopyranosylbenzene (or Pyridine) and Dimannosyl-1,8-diaminooctane - Lee1, Y.G.; Song1, J.H.; Jung2, S.H.; Lee1, E.J.; Lee1, E.S.; Lee1, D.H.; Jung1, D.I.; Hahn3, J.T. (Asian Journal of Chemistry, 2011)
The one-pot synthesis of divalent of mannose disaccharides, of potential use as anti-infective agents against enterobacteria infections, is described. We report one-pot synthesis of dimannopyranosylbenzenes (6, 7, 8), dimannosyl-2,6-diamino-pyridine (9) and dimannosyl- 1,8-diaminooctane (10). But the reaction of 8-(2-amino-pyridin-3-yl)-8-azabicyclo[3.2.1]octane-3-one (11) as a monoamine and D-(+)- mannose did not occur. The results implied that compound 12 is not produced due to steric hindrance of tropane ring.